Young Pacific Male Rugby Players' Perceptions and Experiences of Mental Wellbeing - Caleb Marsters; Jemaima Tiatia-Seath (MDPI AG, 2019)
Recent studies and increased media reporting across Australasia have linked young Pacific male elite athletes to depression, suicide, and other adverse mental health-related events. Despite these accounts, little is known about the way this group experience emotions and mental wellbeing. The aim of this study was to explore young Pacific male athletes’ perceptions and experiences of emotions and mental wellbeing. This qualitative study involved 20 face-to-face interviews with young Pacific males (16–24 years) engaged in elite rugby union and rugby league programmes in Auckland, New Zealand. The results identified that athletes defined mental wellbeing in a holistic and relational manner and perceived mental wellbeing as the culmination of several interconnected factors, including: Family support, reciprocating family support, living a ‘well-balanced’ life, athletic performance, and personal development away from sports. The maintenance of a well-balanced athletic identity and positive social relations were deemed central to sustaining mental wellbeing for these young men.